INCREASED APOPTOSIS SKULL OF PUPS BORN TO TOXOPLASMA GONDII-INFECTED MICE ASSOCIATED WITH INCREASED EXPRESSION OF INTERFERON GAMMA, BUT NOT TUMOR NECROSIS FACTOR ALFA - Suwanti, Lucia Tri; Mufasirin, Mufasirin (African Journal of Infectious Diseases (AJID), 2018)
Bacground: Toxoplasma gondii is an intracellular obligate protozoan parasite that infects most warm-blooded animals including humans. It can cause congenital infection with clinical symptoms ranging from mild to severe including microcephaly. At the cellular level, infection T. gondii causes apoptosis in some tissues and it is induced by proinflammatory cytokines, such as IFN-γ and TNF-α. The purpose of this study is to determine the role of proinflammatory cytokines (TNF-α and IFN-γ) to apoptosis skull of newborn from T. gondii-infected mice. Materials and Methods: Twenty pregnant mice were divided into two groups. The first group was the control group which was not infected with T. gondii tachizoites. The second group was the infected mice, which was infected with T. gondii tachizoites on the day 11.5 of gestation. All mice were cared until delivery. Subsequenly, pups of the mice were sacrificed and their skullcap tissues were taken for histological preparation. The tissues were stained by TUNEL Assay and IHC. Observed variables were apoptotic index and the percentage of skull cell expressing TNF-α and IFN-γ. Data were analyzed with t-test and regression. Results: Compared to the control group, the skull of the pups born to T. gondii-infected mice showed that the number of apoptotic index and percentage of expressing TNF-α and IFN-γ cells were higher than the control group. There is no correlation between increasing expression of TNF-α and apoptosis skull of pups. However, an increasing expression of IFN-γ affected the increased apoptosis of skull pups born to T.gondii-infected mice. Conclusion: Congenital toxoplasmosis in mice increased apoptotic index of skull and the apoptosis of skull associated with increasing expression of IFN-γ, but not associated with increasing expression of TNF-α.